To subtract 1/2(z+4)−3(1/4z+1), we need to first distribute the coefficients outside the parenthesis.
1/2(z+4) = 1/2 * z + 1/2 * 4 = 1/2z + 2
3(1/4z+1) = 3 * 1/4z + 3 * 1 = 3/4z + 3
Now we can subtract the two expressions:
1/2z + 2 - (3/4z + 3)
To combine like terms, we need to find a common denominator, which in this case is 4:
(1/2z * 4/4) + (2 * 4/4) - (3/4z + 3)
= 4/8z + 8/4 - 3/4z - 3
Now we can combine like terms:
(4z + 16 - 3z - 12) / 8z
= (4z - 3z + 16 - 12) / 8z
= (z + 4) / 8z
The final answer in fraction form is (z + 4) / 8z.
Subtract 1/2(z+4)−3(1/4z+1) . Use fractions in final form. pls show answer
1 answer